1998
DOI: 10.1016/s0006-3495(98)77683-0
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Phosphate Release after Photoliberation of Adenosine 5′-Triphosphate in Slow and Fast Skeletal Muscle Fibers

Abstract: Inorganic phosphate (Pi) release was determined by means of a fluorescent Pi-probe in single permeabilized rabbit soleus and psoas muscle fibers. Measurements of Pi release followed photoliberation of approximately 1.5 mM ATP by flash photolysis of NPE-caged ATP in the absence and presence of Ca2+ at 15 degrees C. In the absence of Ca2+, Pi release occurred with a slow rate of 11 +/- 3 microM . s-1 (n = 3) in soleus fibers and 23 +/- 1 microM . s-1 (n = 10) in psoas fibers. At saturating Ca2+ concentrations (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 51 publications
5
41
3
Order By: Relevance
“…Caged isoprenoid diphosphates 5 and 9 meet these criteria. In addition, their uncaging kinetics are comparable with many other commercially available and previously reported caged enzyme substrates/inhibitors and signaling molecules (see Table 1) (47–52). Caged ATP (molecular probes) has been widely used to study the mechanism of ATPases (49,50) and the molecular basis of skeletal muscle fiber contraction (48,52).…”
Section: Discussionsupporting
confidence: 78%
“…Caged isoprenoid diphosphates 5 and 9 meet these criteria. In addition, their uncaging kinetics are comparable with many other commercially available and previously reported caged enzyme substrates/inhibitors and signaling molecules (see Table 1) (47–52). Caged ATP (molecular probes) has been widely used to study the mechanism of ATPases (49,50) and the molecular basis of skeletal muscle fiber contraction (48,52).…”
Section: Discussionsupporting
confidence: 78%
“…If we assume that at 35% of maximal isometric force only 35% of the cross bridges are functioning and a myosin subfragment I concentration of 150 M (7), then ATP splitting per cross bridge would amount to 65, 34, and 21 s Ϫ1 during the 2-, 5-, and 10-s contractions, respectively, at 30°C. These values are similar to or higher than those reported in the literature for isometric contractions after adjusting for temperature (assuming a Q 10 of 2.5 for myosin ATPase) (3,5,6,8,10).We find the skepticism expressed by Barclay and Loiselle and the exchange of views in these letters to be refreshing and hope that this exchange will stimulate physiologists to take a more active interest in the field of muscle energetics. Ultimately, however, independent verification in the form of hard data collected during relevantly designed experiments will be required to settle the issue.…”
supporting
confidence: 80%
“…Our model is based on earlier kinetic descriptions of the actomyosin cycle, which seek to account for both the biochemical steps and force production (for example Pate & Cooke, 1989;He et al 1998b;He et al 2000;Wang & Kawai, 2001). Unlike these models, our model includes the effects of performance of work and activation, and it describes energy production as well as the release of P i and ADP.…”
Section: Energetics: Kinetic Modelmentioning
confidence: 99%
“…This energy output comes principally from the ATPase activity of the actomyosin system and that of the sarcoplasmic reticulum Ca 2+ pump, and to a lesser extent from other energy-producing processes. Measurements of P i release by permeabilized muscle fibres have shown that the rate of the P i release step in the actomyosin cycle decreases considerably during the first few turnovers (He et al 1998b and references therein). The ADP release has been measured much later in an isometric contraction, while force is maintained at the plateau level (Hilber et al 2001); the rate is constant in this period, but much lower than that measured at the start of activation.…”
mentioning
confidence: 99%